Innovation, Internationalization and Entrepreneurship - Renata Korsakienė; Hasan Dinçer; Serhat Yüksel (MDPI, 2021)
Over the past years, businesses have had to tackle the issues caused by numerous forces from political, technological and societal environment. The changes in the global market and increasing uncertainty require us to focus on disruptive innovations and to investigate this phenomenon from different perspectives. The benefits of innovations are related to lower costs, improved efficiency, reduced risk, and better response to the customers' needs due to new products, services or processes. On the other hand, new business models expose various risks, such as cyber risks, operational risks, regulatory risks, and others. Therefore, we believe that the entrepreneurial behavior and global mindset of decision-makers significantly contribute to the development of innovations, which benefit by closing the prevailing gap between developed and developing countries. Thus, this Special Issue contributes to closing the research gap in the literature by providing a platform for a scientific debate on innovation, internationalization and entrepreneurship, which would facilitate improving the resilience of businesses to future disruptions
Keywords: 650; eco-innovation; internationalisation; risk; performance; bibliometric analysis; Mass Customization; mass personalization; digitalization; risk management; bibliometric; Web of Science; airsoft industry; customer satisfaction; country of origin; entrepreneurship; value co-creation; value proposition; process; business process management; quality management; total quality management; Lean; Six Sigma; ISO 9000; mixed methods research; mixed research approaches; mixed research models; innovations; innovation management; civilian-military cooperation; emergency management; emergency preparedness; rescue system; state of emergency; threats; real options; synergy; acquisition; dynamic capabilities; business model; the ICT industry; capital structure; capital structure theories; capital structure decisions; financial management; external financing; corporate value; finance management; management; innovative work behavior; business performance; cognitive diversity; teamwork climate